2019
DOI: 10.1080/14728222.2019.1580692
|View full text |Cite
|
Sign up to set email alerts
|

Biology and targeting of the Jumonji-domain histone demethylase family in childhood neoplasia: a preclinical overview

Abstract: Introduction: Epigenetic mechanisms of gene regulatory control play fundamental roles in developmental morphogenesis, and, as more recently appreciated, are heavily implicated in the onset and progression of neoplastic disease, including cancer. Many epigenetic mechanisms are therapeutically targetable, providing additional incentive for understanding of their contribution to cancer and other types of neoplasia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 190 publications
(259 reference statements)
2
15
0
Order By: Relevance
“…The transcriptome data are summarized in Figs 2A and . Consistent with the known functions of KDM3A and Ets1 as activators of gene expression [11,19], and with Ets1 downstream of KDM3A [12], approximately one third of genes positively controlled by KDM3A were also positively regulated by Ets1, while roughly one half of genes positively controlled by Ets1 were also positively regulated by KDM3A, in each cell line (Figs 2A and ). The KDM3A and Ets1 regulated transcriptomes showed substantial conservation between the two different FP‐RMS cell lines, with approximately one third of all genes positively controlled by each factor in Rh41 cells also similarly regulated in Rh30 cells, and, conversely, nearly two thirds of KDM3A positively controlled genes and one half of Ets1 positively controlled genes in Rh30 cells showing similar regulation in Rh41 cells (Figs 2A and ).…”
Section: Resultssupporting
confidence: 83%
“…The transcriptome data are summarized in Figs 2A and . Consistent with the known functions of KDM3A and Ets1 as activators of gene expression [11,19], and with Ets1 downstream of KDM3A [12], approximately one third of genes positively controlled by KDM3A were also positively regulated by Ets1, while roughly one half of genes positively controlled by Ets1 were also positively regulated by KDM3A, in each cell line (Figs 2A and ). The KDM3A and Ets1 regulated transcriptomes showed substantial conservation between the two different FP‐RMS cell lines, with approximately one third of all genes positively controlled by each factor in Rh41 cells also similarly regulated in Rh30 cells, and, conversely, nearly two thirds of KDM3A positively controlled genes and one half of Ets1 positively controlled genes in Rh30 cells showing similar regulation in Rh41 cells (Figs 2A and ).…”
Section: Resultssupporting
confidence: 83%
“…Specifically, we showed that, in Ewing Sarcoma, an aggressive pediatric cancer of bone and soft tissue, KDM3A acts as both a tumor promoter [7], and, through its downstream-induced gene MCAM, a promoter of metastasis [8]. KDM3A has also been shown to be upregulated in expression, and to be involved in diseasepromoting properties, in numerous other cancers (as recently reviewed in [9]). This, along with its restricted expression and relative paucity of essential functions, has pointed to KDM3A as a potentially attractive therapeutic target [10].…”
Section: Rhabdomyosarcomamentioning
confidence: 87%
“…Our findings support further evaluation of JIB-04 action in FP-RMS, and potentially other fusion-driven sarcomas. Notably, since its identification only a few years ago, JIB-04 has at this point been shown to have activity against a number of different cancers, including chemoresistant disease (as recently reviewed [9]).…”
Section: Discussionmentioning
confidence: 99%
“…The best studied of these is the overexpression of KDM5B observed in breast cancer and melanoma, which correlates with poor prognosis (Han et al, 2017). Despite being shown to directly or indirectly regulate genes involved in cell cycle progression, cancer stem cell survival and DNA repair, no clear model has emerged to explain its oncogenic capacities (Catchpole et al, 2011;Han et al, 2017;McCann et al, 2019;Roesch et al, 2013;Yamamoto et al, 2014;Yamane et al, 2007). Our lack of understanding of KDM5-regulated pathways that lead to clinical disorders underscores the importance of defining the physiological functions of KDM5 proteins.…”
Section: Introductionmentioning
confidence: 99%